Analysis of socio and economic factors that shape citizens attitude towards immigrants: EU case - Gedaminské, Giedré (2021)
The main aim of this thesis is to measure social and economic factors which have the greatest impact on tolerance of population to immigrants in European Union countries and to figure out how attitudes towards immigrants changed in the period between 2002 and 2016. For this reason is analyzed data from the European Social Survey, OECD, the World Bank and Knoema databases for 25 European countries. Though the analysis of scientific works are identified macro and personal factors which could affect tolerance. As macro variables in research are considered to use the unemployment rate, GDPpc, FDI and crime situation in the country, as personal variables are considered the respondent’s age, gender, marital status, level of education, work situation, religiosity, interest in politics, importance of traditions, feel of safety, satisfaction in country’s economy and life in general. For calculations are used ordinary least and ordered logit econometrical models and calculations are made using Eviews software. The results demonstrated that in general tolerance towards immigrants increased during the period and personal situation is more influencing tolerance than macro factors in hosting country but the significance of factors and direction of relations differ across the countries.